2022
DOI: 10.3390/ijms232314852
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Unstable HLA-C Variants in HIV-1 Rapid-Progressor Patients

Abstract: HIV-1 infection in the absence of treatment results in progression toward AIDS. Host genetic factors play a role in HIV-1 pathogenesis, but complete knowledge is not yet available. Since less-expressed HLA-C variants are associated with poor HIV-1 control and unstable HLA-C variants are associated with higher HIV-1 infectivity, we investigated whether there was a correlation between the different stages of HIV-1 progression and the presence of specific HLA-C allotypes. HLA-C genotyping was performed using alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(42 reference statements)
1
0
0
Order By: Relevance
“…We found that the HIV-infected individuals had an inverse association between HIV-1 viral load and CD4 + T cell count. Further, the progressors had a significantly higher VL and reduced CD4 count as compared to the LTNPs, as also previously reported [99][100][101]. Association studies have further shown that type-1 IFNs-IFN-α and IFN-β, were inversely correlated with viral load and positively correlated with CD4 count.…”
Section: Discussionsupporting
confidence: 83%
“…We found that the HIV-infected individuals had an inverse association between HIV-1 viral load and CD4 + T cell count. Further, the progressors had a significantly higher VL and reduced CD4 count as compared to the LTNPs, as also previously reported [99][100][101]. Association studies have further shown that type-1 IFNs-IFN-α and IFN-β, were inversely correlated with viral load and positively correlated with CD4 count.…”
Section: Discussionsupporting
confidence: 83%
“…The results showed a significant correlation between rapid progression to AIDS and the presence of two or one unstable HLA-C variants. Thus, unstable HLA-C variants both at genotype and at allele levels and rapid progression to Aids [71].…”
Section: Discussionmentioning
confidence: 99%